Load response towards voltage in TNB power system using the measurement approach - Bakar, A.H.A.; Yusof, S.; Satchiananda, M.; Mekhilef, Saad (2006)
This paper reports the load-voltage dependency using field measurements for a faulted condition that caused a momentary voltage sag in a Tenaga Nasional Berhad network in the Central Region. The static load model is used in this study and its suitability is discussed in comparison to the dynamic load model. A fast method of calculating real and reactive power based on available information is devised. Propagation of fault through transformers is also investigated. The effect of voltage on real and reactive power is discussed at great length. Various factors influence the load characteristic, including weather, time of day, network conditions and type of feeder load. Long-term steady state data should be made available for analysis to back up results from this study.